Explaining climate policies' popularity—An empirical study in four European countries. Issue 92 (February 2019) - Bothner, Fabio; Dorner, Florian; Herrmann, Alina; Fischer, Helen; Sauerborn, Rainer
Highlights: Analyzes European household's willingness to mitigate climate change through changes in consumption behavior. New analytical perspective through Qualitative Comparative Analysis in large-N design. Highlights the contribution of health information for willingness to mitigate. Demonstrates limitations of financial incentives to motivate behavioural change. Points to need for different policy design to motivate household mitigation of GHG emissions. Abstract: The climate change mitigation potential of the production side has been discussed very frequently, but private citizens and households have received less systematic attention. Thus, this paper focuses on the willingness of private households to reduce their greenhouse gas emissions. While many scholars study the socio-economic characteristics of people to then recommend policies, we change the analytical perspective and look at the characteristics of climate mitigation actions that affect households' willingness to adopt these measures: Costs, emission reductions, behavioral change, and consumption sector. The paper uses data from HOPE ( HOusehold Preferences for reducing greenhouse gas emissions in four European high-income countries ), an interdisciplinary project investigating households' preferences for reducing greenhouse gas in four countries (France, Germany, Norway and Sweden). We use a fuzzy-set QCA (fsQCA) to analyze which attributes are necessary or sufficient conditions for specific actions to be selected by participants of HOPE. The results of the fsQCA show that Food & Recycling actions are particularly popular. The general pattern that was found shows that people prefer actions that are easy to implement even though they often do not reduce the CO2e-Footprint by much. Therefore, the condition Behavioral Change is the most important lever in improving households' willingness to act on climate change. Moreover, the analysis of Health Information suggests that there is an urgent need to go beyond financial arguments in future research.